Indosat’s Rebranding According to Stakeholders' View - Pambayun Galih Waskitha; Nuriyatul Lailiyah, S.Sos, M.I.Kom (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Rebranding, an attempt or enterprise which is undertaken by the company or institutions to completely change or renew an existing brand to make it better. Rebranding is not just a logo change, but also includes; the change of messages, change of how aprroaching consumers, providing new services, or even changes about what has promised to the consumers. One of the reasons why Indosat conducted a rebranding due to the change of management / strategy occurs in the company, such as changes in leadership or merger; or it can be purchased of a company through the other hand, became one of the strong reason to conduct a rebranding. Therefore, the aim of this study is to describe how to think about stakeholders responding the rebranding conducted by Indosat, especially the external stakeholders. All forms of information and new services, obtained by the community during the Indosat’s rebranding process, those are divided into several stakeholders experienced the difference in the admission process and ways of thinking about rebranding information. According to Elaboration Likehood Models related with the persuasive message. Indosat’s rebranding information was received by the stakeholders as a new message. In accordance with the Elaboration Likehood Models’s stages, the results of this study indicate that Indosat’s rebrandring message information is processed only at the stage “ability to process” by the most of the stakeholders. They choose to take the peripherals path as low motivation of the persuasive message, because they consider the communication needs, include in the low-involvement. The stakeholders consider that communication is an important requirement, but not considered as a necessity that requires high attention and involvement in making a purchasing decision. The rest, the other stakeholders also appreciate that Indosat’s decision is appropriate and successful, seen from the mutual cooperation that they can build in their attempt for being the best provider in Indonesia.